Comprehensive computational analysis reveals YXXΦ[I/L/M/F/V] motif and YXXΦ-like tetrapeptides across HFRS causing Hantaviruses and their association with viral pathogenesis and host immune regulation - Noor, Fatima; Ashfaq, Usman Ali; Asif, Muhammad; Adeel, Muhammad Muzammal; Alshammari, Abdulrahman; Alharbi, Metab (Frontiers in Immunology, 2022)
Hemorrhagic fever with renal syndrome (HFRS) is an acute zoonotic disease transmitted through aerosolized excrement of rodents. The etiology of HFRS is complex due to the involvement of viral factors and host immune and genetic factors. The viral species that dominantly cause HFRS are Puumala virus (PUUV), Seoul virus (SEOV), Dobrava-Belgrade virus (DOBV), and Hantaan virus (HTNV). Despite continuous prevention and control measures, HFRS remains a significant public health problem worldwide. The nucleocapsid protein of PUUV, SEOV, DOBV, and HTNV is a multifunctional viral protein involved in various stages of the viral replication cycle. However, the exact role of nucleoproteins in viral pathogenesis is yet to be discovered. Targeting a universal host protein exploited by most viruses would be a game-changing strategy that offers broad-spectrum solutions and rapid epidemic control. The objective of this study is to understand the replication and pathogenesis of PUUV, SEOV, DOBV, and HTNV by targeting tyrosine-based motif (ΥXXΦ[I/L/M/F/V]) and ΥXXΦ-like tetrapeptides. In the light of the current study, in silico analysis uncovered many different ΥXXΦ[I/L/M/F/V] motifs and ΥXXΦ-like tetrapeptides within nucleoproteins of PUUV, SEOV, DOBV, and HTNV. Following that, the 3D structures of nucleoproteins were predicted using AlphaFold2 to map the location of ΥXXΦ[I/L/M/F/V] motif and ΥXXΦ-like tetrapeptides in a 3D environment. Further, in silico analysis and characterization of Post Translational Modifications (PTMs) revealed multiple PTMs sites within ΥXXΦ[I/L/M/F/V] motif and ΥXXΦ-like tetrapeptides, which contribute to virulence and host immune regulation. Our study proposed that the predicted ΥXXΦ[I/L/M/F/V] motif and ΥXXΦ-like tetrapeptides may confer specific functions such as virulence, host immune regulation, and pathogenesis to nucleoproteins of PUUV, SEOV, DOBV, and HTNV. However, in vivo and in vitro studies on ΥXXΦ[I/L/M/F/V] motif and ΥXXΦ-like tetrapeptides will assign new biological roles to these antiviral targets.